2021
DOI: 10.3390/toxics9110304
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Accumulation in Commercial Varieties of Oryza sativa L. Cultivated in Soils of La Mojana Region, Colombia

Abstract: The Hg accumulation in different commercial varieties of Oryzasativa L. was evaluated in the region of La Mojana, Colombia, where rice cultivation has become the staple food of the population living in this area. The varieties studied were Fedearroz-473 (FA473), Fedearroz-2000 (FA2000), and Fedearroz-Mocari (FAM). Soil spiked at different Hg levels was evaluated, (130, 800, and 1500 µg kg−1) using a 32 factorial design that consisted of 3 (rice varieties) × 3 (Hg contents). The biomass, 1000-grain weight, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Previous health risk assessments in the study area have focused on exposure to mercury from fish consumption and have shown that the estimated weekly intake for children and women of childbearing age was above the provisional tolerable weekly intake (Marrugo-Negrete et al 2020). In the Mojana area, the other exposure pathway assessed was rice consumption, but the mercury HQ values were always < 1 (Enamorado-Montes et al 2021).…”
Section: Human Health Risk Assessmentmentioning
confidence: 96%
“…Previous health risk assessments in the study area have focused on exposure to mercury from fish consumption and have shown that the estimated weekly intake for children and women of childbearing age was above the provisional tolerable weekly intake (Marrugo-Negrete et al 2020). In the Mojana area, the other exposure pathway assessed was rice consumption, but the mercury HQ values were always < 1 (Enamorado-Montes et al 2021).…”
Section: Human Health Risk Assessmentmentioning
confidence: 96%
“…The Mojana region. translated into contamination of different animal species and water bodies (Pedraza and Espinosa-Ramírez, 2022;Gutiérrez-Mosquera et al, 2021;Alonso et al, 2014Alonso et al, , 2020, and specifically in the Mojana region, which put biodiversity and human health at risk (Enamorado-Montes et al, 2021;Galeano-Paez, 2021;Buelvas-Soto et al, 2022). Similarly, regarding human exposure, several associated evidences have been reported in Colombia in which these contaminant levels were above the reference value considered safe presenting indicators from 1.87 μg/g to 22.98 μg/g for Hg in hair (Manjarres-Suárez & Olivero-Verbel, 2020;Salazar-Camacho et al, 2017;Valdelamar-Villegas and Olivero-Verbel, 2019) and between 5.5 μg/L 14.63 μg/L for Hg in blood (Díaz et al, 2018;Gutiérrez-Mosquera et al, 2018), as of high concentrations for As in blood, especially for inhabitants near areas of mining activity (Cruz-Esquivel et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Colombia is one of the countries that pollutes the most with mercury, and in 2021 was considered the fourth largest gold producer in Latin America, with a production of 76.8 tons, representing an increase of 17% compared to production in 2020 [8]; it was also considered to hold the first place in per capita pollution in the world [9]. Concern about inappropriate practices and excessive use of mercury in informal and illegal mining and their threat to Colombian fish biodiversity is growing daily [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The biotransformation of inorganic mercury species to methylated organic species in water bodies can occur in the sediment and in the water column [25]. Factors such as concentration, pH, temperature, presence of organic matter, microbial activity, dissolved oxygen, and type of sediments can affect the toxicity and speciation of mercury in the aquatic environment [13,24]. The intake of heavy metals by fish and accumulation in the organism result in alterations in the structure and function of different tissues and vital organs [26].…”
Section: Introductionmentioning
confidence: 99%